The Hyperreality of Political Power: Political Condition of Indonesia During Pandemic in the Postmodern Era - Sirojjudin, Achmad Maulana; Suryadipta Wardhana, Anak Agung Ngurah Agung (Faculty of Da'wa and Communications Sciences, 2024)
This article discusses Indonesia’s political power regarding policies dealing with the Covid-19 pandemic crisis through a postmodern perspective. Disruption of information as one of the characteristics of postmodernism has shown us that various media can mix all realities. The use of various media has made individuals experience confusion in drawing a real reality. A hyperreal form of meaning replaces the existing reality because it is formed by individual narratives replacing metanarratives. Meanwhile, factual truth has also been replaced by alternative truths that are the favorites of everyone. This study uses a qualitative descriptive analysis method through literature studies, instrumental case studies, and phenomenology. Facts and truth have become biased, saturated into more micro and individual forms, so individuals now have autonomy over their truth. This truth is due to hyperreality, where the sign becomes more real than reality itself. The Indonesian government’s policy regarding this pandemic is a reality that individuals want to abandon or take up. This dynamic form is currently happening in Indonesian society. Regarding the pandemic, the community has its own narrative in assessing vaccines as a tool to eradicate the spread of the Covid-19 pandemic.